Studi Kasus Sebagai Salah Satu Proses Belajar di Perguruan Tinggi - V. J. Wisnu Wardhono (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
To prepare the academician degree-holder is not enough by giving them the theory based from the text-book only. Like Alfred North said, what the faculty has to cultivate is activity in the presence of knowledge. What the students have to learn is activity in the presence of knowledge. In this context the lecturer must shifting the paradigm and rejecting the doctrine that student should first learn passively, and then having learned, should apply knowledge. It is psychological error. And now the question is, what should we do as faculty member to prepare the academician degree-holder for entering the real business world after they graduated from this faculty? In this article the writer will describe the difference between learning (by case study) and teaching, the reader can also find the learning objectives and learning process in study with cases. And last but not least the writer will describe how to write the case for lecturing material.